Integrating the Technology in Teaching and Learning Process Through Digital Media Creation as A Way to Improve Indonesian EYL Teachers’ Competence - Shirly Rizki Kusumaningrum; Utami Widiati; Khoirul Anwar; Hernik Farisia (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
Abstract: Now that the spread of Covid 19 is still high and the teaching and learning process should be continued to be conducted at homes, but it seems that some teachers –in this case EYL teachers– are not ready to integrate various digital platforms. It is necessary for us to respond to the need of investigating technology readiness of English for young learners teachers in teaching during this Covid 19 pandemic. It is strongly important to reveal the teachers’ technology readiness as it plays vital role, especially during this pandemic —when the only thing that the teachers and the students can do is interacting online. Without having adequate literacy in technological thing, it is impossible to create teaching and learning process which can facilitate both the teachers and the students. Based on the result of initial survey, it could be stated that some teachers might not be ready in integrating the technology in their virtual classrooms; ending up in either providing lots of assignments or creating monotonous activities, which of course break the nature of teaching English for young learners. Hence, it is expected that by conducting this study, the researchers could assist some of the teachers to be more aware with their technology readiness, so that they could serve the students better, and the students could also learn the material more interesting and meaningful.